Forecasting the Price of Curly Red Chilies in Malang Regency With Using the ARIMA Method: Peramalan Harga Cabai Merah Keriting Di Kabupaten Malang Dengan Menggunakan Metode ARIMA - Nur Hanifah Ibrahim; Burhanuddin Izzul Salam; Indah Mafaati Nur (Department of Sains Data UNIMUS Universitas Muhammadiyah Semarang, 2025)
CChile is one of the hultikura plants that grows abundantly in Indonesia. In Indonesia, chilies are widely used as a cooking spice, making them a household staple. The increasing need for chilies (during the holidays) causes the demand for chilies to also increase. The increase in chile prices which is not directly proportional to chile production causes price changes. To maintain optimal availability of chilies, forecasting is needed to help make decisions and develop policies. One method that can be used for forecasting is the Autoregressive Integrated Moving Average (ARIMA) method. Based on the analysis results obtained, the best ARIMA model used in this research is the ARIMA model (0, 1, 0) which produces the smallest AIC value and MAPE of 2.664656%, the accuracy value is less than 10% which means that the forecasting ability with the ARIMA (0, 1, 0) model is very good.